(untitled) (International Seven Journal of Multidisciplinary, 2024)
Objectives: To evaluate which diagnostic methods are most effective for the early assessment of possible cardiac anomalies in utero and in the neonatal period, with the aim of analyzing the impact of tests performed during prenatal care and correlating early diagnosis with the risk of infant mortality. Method: a systematic review was carried out using the Science and Pubmed platforms in the period between 2012 and 2022, where ’newborns’ OR ’premature infants’ AND ’congenital heart disease’ OR ’congenital heart defects’ OR ’congenital heart defects’ were used in the search” OR “baby’s heart” AND “early diagnosis” OR “prenatal diagnosis”. Successively, the articles found were selected according to the previously determined inclusion and exclusion criteria to suit the type of research. Results: after analyzing 97 articles, 23 were in the same parameters and were considered in the study, addressing exams such as ultrasound, nuchal translucency, fetal echocardiogram, genetic tests, pulse oximetry, cardiovascular physical examination and echocardiographic reassessment. Conclusion: given the assumption, it was found that prior identification of the pathological change results in a more improved and prepared therapeutic plan and better psychological acceptance by parents. Therefore, the importance of disseminating the various methods available and how to perform them correctly is justified in order to make an early diagnosis of congenital heart diseases and contribute to reducing the mortality of these newborns.